The use of remote microphone systems in unilateral hearing loss: a preliminary study among Brazilian children and teenagers (Journal of Applied Oral Science, 2022)
Due to the large number of individuals with Unilateral Hearing Loss (UHL) and the recommendation to use hearing assistive devices, studies are required to define possibilities of intervention for this population. Objective: To evaluate the performance of the Remote Microphone System (RMS) in children with UHL. Methodology: Prospective clinical study with a convenience sample. Eleven children (mean age of 9.2 years) with severe and profound sensorineural UHL, hearing aid users and enrolled in regular schools participated in the study. They were evaluated using the Hearing in Noise Test (HINT), the Classroom Participation Questionnaire (CPQ), and the Sustained Auditory Attention Ability Test (SAAAT) with RMS. Results: HINT results were analyzed using variance to three criteria of repeated measures, which revealed differences between intervention, position, and time factors and significant interaction between these three factors. The comparative analysis of the results from CPQ showed significant differences in the statistical t-test (p=<0.001) for all subscales. The analysis of variance at two repeated measures criteria used in the study of SAAAT revealed a difference between intervention and time, and both interacted significantly. Conclusion: The RMS associated with a hearing aid was effective for individuals with UHL.